The fiscal lifetime cost of receiving refugees - Joakim Ruist (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2019)
This study estimates the fiscal consequences of receiving refugees, over the refugees' lifetime. It uses data from Sweden in 2015, and the calculations account for refugees' age, years since immigration, and country of origin. The estimated average annual fiscal net contribution over the lifetime of the average refugee (58 years) ranges from -12 per cent of GDP per capita for refugees from the countries of origin for which labor market performance has historically been the strongest, to -22 per cent for those for which it has been the weakest. The estimates imply that if the European Union received all refugees currently in Asia and Africa, the implied average annual fiscal cost over the same time span would be at most 0.6 per cent of GDP.
Keywords: F22; H20; H50; J61; 330; refugees; immigration; public finances